If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 11) = 2(2x + -6) Reorder the terms: -1(11 + x) = 2(2x + -6) (11 * -1 + x * -1) = 2(2x + -6) (-11 + -1x) = 2(2x + -6) Reorder the terms: -11 + -1x = 2(-6 + 2x) -11 + -1x = (-6 * 2 + 2x * 2) -11 + -1x = (-12 + 4x) Solving -11 + -1x = -12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -11 + -1x + -4x = -12 + 4x + -4x Combine like terms: -1x + -4x = -5x -11 + -5x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 -11 + -5x = -12 + 0 -11 + -5x = -12 Add '11' to each side of the equation. -11 + 11 + -5x = -12 + 11 Combine like terms: -11 + 11 = 0 0 + -5x = -12 + 11 -5x = -12 + 11 Combine like terms: -12 + 11 = -1 -5x = -1 Divide each side by '-5'. x = 0.2 Simplifying x = 0.2
| 5*(1/3)-(-2/3)X | | 2(6x-1)=120 | | -30=-14+v | | 4x=4(0+2x) | | 6x+68=9x-7 | | 2x+20+3x+8=180 | | -3=x-15 | | 9sin^2x+2=3 | | 2=2n | | 1x-20=10 | | b-5=-24 | | 5x+85=53 | | (36x)/(-8x) | | 2x+1=6x+(-23) | | 3k=-51 | | 3n+4=7n+4 | | 2+25x=20x+15 | | 3.4x=2.7 | | 5t+6=-24-t | | 36x/-8x | | b/3--17=20 | | y=-0.02x^2+1.6x | | 9x+9=8x+5 | | -2x-8x= | | 3(x-5)=2x+30 | | 2.7x-0.05x+0.75x=3.4x | | v/3-3=1 | | 36x=-8x | | 25b^4-211b^2+3024=0 | | 3(n-2)=3(2n+4) | | -10+2j=-2 | | 6x(4+3)= |